Beyond the Neomaterialist Divide: Negotiating Between Eliminative and Vital Materialism with Integrated Information Theory. (December 2018) - Wilson, Alexander
Though most neomaterialists share a commitment to the Copernican decentring of humans from the world stage, there is disagreement on the purposes of such an endeavour. The polemic stems from a fundamental discrepancy about what the return to materiality entails: is matter the principle of the non-thinking as such, or is it always already imbued with some sort of subjectivity? Is the new materialism's goal to come to terms with the non-living origin of life? Or is it rather to recognize that seemingly dead materials are always in some sense incipiently alive? For convenience, we can think of two neomaterialist perspectives: the rationalist or eliminative neomaterialism, and the vitalist or panpsychist neomaterialism. I explore some of the conceptual problems faced by both camps and, drawing from the recently developed theory of consciousness as integrated information (Tononi), as well as its quantum physical construal by Max Tegmark, I suggest some provisional ways to address those issues.